Functional foods and cardiovascular disease - Eskin, N. A. M. [ (Neason Akivah Michael)]; Moghadasian, Mohammed H. (Boca Raton, Florida : CRC Press, 2012)
"Drawn from the latest clinical and experimental information, this book covers cover products enriched with phytosterols, n-3 fatty acids, garlic extract naturally occurring antioxidants, folic acid, CLA, as well as fibers and flavonoids. It describes the connection between diets, dietary habits, and cardiovascular diseases. It also explains how functional food ingredients and nutraceuticals can mitigate cardiovascular disorders. The authors examine recent technologies for generating novel food products enriched with cardiovascular protective dietary agents. They include experimental and clinical evidence of various ingredients"-- Provided by publisher
1. The pathophysiology of coronary artery disease -- 2. Advances in technology to generate cardiovascular-friendly functional food products -- 3. Clinical and experimental evidence on cardiovascular benefits of Fish Oil -- 4. Alpha-linolenic acid and cardiovascular disease: Flaxseed Oil -- 5. Folic acid and pathogenesis of cardiovascular disease -- 6. Experimental and clinical evidence of cardiovascular benefits of plant sterols -- 7. Wine and cardiovascular benefits -- 8. Role of garlic products in reducing cardiovascular risks -- 9. Impact of egg consumption in development or prevention of heart disease -- 10. Fibers and prevention of cardiovascular disease -- 11. Chocolate and cocoa: a comprehensive review on cardiovascular benefits -- 12. Tea and coffee: a concise review of effects on cardiovascular risk factors
Includes bibliographical references and index
Keywords: Cardiovascular system -- Diseases -- Diet therapy; Functional foods